1998
DOI: 10.3109/10715769809066890
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-Modified Low Density Lipoprotein Enhances Human Monocyte Chemotaxis

Abstract: In diabetes mellitus the progression of atherosclerosis is accelerated. The interaction of glucose with atherogenic lipoproteins may be relevant to the mechanisms responsible for this vascular damage. The aim of this study was to examine the effect of glucose-modified low density lipoprotein (LDL) on human monocyte chemotaxis and to investigate the roles of oxidation and glycation in the generation of chemotactic LDL. Cu(II)-mediated LDL oxidation was potentiated by glucose in a dose-dependent manner and incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 43 publications
0
24
0
Order By: Relevance
“…Both native and oxidised LDL bind to mesangial matrix in vitro [24]; therefore, it is possible that mesangial cells in vivo are exposed to both native and oxidised LDL. Glycated LDL has been shown to induce functional changes in various cell types, including enhanced chemotactic properties in monocytes [25,26], stimulated migration and proliferation of smooth muscle cells [27], and increased platelet aggregation, NO production and Ca 2+ -ATPase activity [26,28]. Some information on the effect of native and oxidised LDL in promoting IL6 production in HMCs is available [20], while an extensive comparison of the biological activity of different LDL particles, including glycated LDL, has not been previously performed.…”
Section: Discussionmentioning
confidence: 99%
“…Both native and oxidised LDL bind to mesangial matrix in vitro [24]; therefore, it is possible that mesangial cells in vivo are exposed to both native and oxidised LDL. Glycated LDL has been shown to induce functional changes in various cell types, including enhanced chemotactic properties in monocytes [25,26], stimulated migration and proliferation of smooth muscle cells [27], and increased platelet aggregation, NO production and Ca 2+ -ATPase activity [26,28]. Some information on the effect of native and oxidised LDL in promoting IL6 production in HMCs is available [20], while an extensive comparison of the biological activity of different LDL particles, including glycated LDL, has not been previously performed.…”
Section: Discussionmentioning
confidence: 99%
“…28 Glycation increases the chemotactic activity of LDL for monocytes, which promotes the deposition of monocytes on the endothelial surface. 29 Previous studies by our group indicated that glycated LDL augmented PAI-1 production and reduced tPA generation in vascular ECs. 13 Imbalance between EC-derived PAI-1 and tPA potentially reduces intravascular fibrinolytic activity and enhances thrombotic tendency.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperglycemia, in fact, induces an increase in nonenzymatically glycated LDL (glycLDL), which renders them more susceptible to oxidative stress [38,39]. Moreover, glycLDL may cause platelet dysfunction by an increase in intracellular Ca 2+ concentration and platelet NO production, as well as inhibition of the platelet membrane -ATPase) activity, activation of protein kinase C (PKC), decreased production of nitric oxide (NO), increased formation of reactive oxygen species (ROS) and nonenzymatic glycation of platelet membrane glycoproteins (GPs).…”
Section: Metabolic Alterationsmentioning
confidence: 99%